DISCUSSION ON ABORTION FROM THE CONCEPT OF PERSON - Curtidor Gutiérrez, Natalia (Disertaciones, 2017)
The primary aim of this article is to analyze the arguments infavor and against abortion that have as its main element the concept of person. The main desire is to find a solution to the moral debate about abortion based on the hypothesis that it is not always clear what a person is. Therefore, the arguments built around this concept tend to be in disagreement. That is why it was thought that if it is clear what a person is, it will be clear as well, whether it is possible to put abortion at the same level of murder and to come to clear conclusions on the issue.